Case analysis: Spanish and Anglo-Saxon paradigms in the academic approach to the press coverage of traumatic events. - Fernández González, Virginia María (Historia y Comunicación Social, 2014)
Covering traumatic events, such as terrorist attacks or natural disasters, is a hard task that requires previous preparation from the journalists given that, in many cases, they are subject to added and significant pressure which affects the way in which they depict the nature of the situation and, most of all, the state of the victims. The following report is an exploratory study on the levels of journalism registered on the European Higher Education Area of the Spanish country, and also of three other English-speaking countries with the purpose of ascertaining if there is an academic course that addresses these kind of aspects.
Keywords: Crisis situation; natural disaster; EHEA; journalism studies; trauma; influence on the audience.